Does lower-limb asymmetry increase injury risk in sport? A systematic review. (May 2021) - Helme, Mark; Tee, Jason; Emmonds, Stacey; Low, Chris
Abstract: Objective: The aim of this review was to synthesize the current understanding relating to the risks of lower body functional asymmetry with injury in athletic populations. Methods: An iterative data mining and sampling approach was used to construct a search phrase from key words, which were used to identify studies within SPORTdiscus, Medline and Academic Search Complete databases. Additional references were sourced from the reference lists of these articles. Results: After screening, 31 papers were reviewed, from an initial search identifying 302 possible studies. A total of 6228 participants were involved in the studies, of which soccer players were the most observed sporting demographic (n = 2171). Of the 31 studies reviewed eight found no statistical association between lower limb asymmetry and injury risk, 10 studies provided partial statistically significant evidence and a further 10 provided statistically significant statistical links. Conclusion: Overall moderate to lower quality evidence for functional asymmetry as a risk factor for injury in sport was observed. While the possibility of a relationship between lower limb functional asymmetry and injury risk cannot be ruled out, further higher quality investigations, adopting standardised methodologies, is required. Highlights: Research evidence suggests there is low to moderate level evidence for association between asymmetry and injury. Methodological approaches are inconsistent, specifically to the way in which asymmetry data is collected and analyzed. Methods of injury aetiology analysis require a more contemporary, multivariate statistical approach.